2013
DOI: 10.1002/ejic.201300995
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Reactions of Ni and Pd Hydroxo Pincer Complexes [(iPrPCP)M–OH] with CO2: Solid‐State Study of the Decarboxylation of the Monomeric Bicarbonate Complexes [(iPrPCP)M–OCOOH] (M = Ni, Pd)

Abstract: Monomeric Ni and Pd hydroxides stabilized by the iPrPCP pincer ligand react with CO2 to give labile terminal bicarbonate complexes that readily lose CO2 and water to give binuclear carbonate complexes. Differential scanning calorimetry (DSC) has been used to monitor the decomposition of both bicarcabonates in the solid state. When the carbonate complexes are heated under reflux in thf in the presence of water, full decarboxylation takes place, restoring the starting hydroxides and demonstrating that CO2 insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…This is diagnostic of a metal bicarbonate structure ( 10 , Scheme ) rather than a carbonate ( 11 , Scheme ) 8. 19 To gain further insight into the identity of the product, we performed diffusion‐ordered NMR spectroscopy (DOSY) experiments on the starting material 9 and the product in solution. The experiments indicated very similar diffusion coefficients in CDCl 3 (8.37±0.57×10 −10 m 2 s −1 for 9 and 7.54±0.25×10 −10 m 2 s −1 for the product).…”
Section: Resultsmentioning
confidence: 99%
“…This is diagnostic of a metal bicarbonate structure ( 10 , Scheme ) rather than a carbonate ( 11 , Scheme ) 8. 19 To gain further insight into the identity of the product, we performed diffusion‐ordered NMR spectroscopy (DOSY) experiments on the starting material 9 and the product in solution. The experiments indicated very similar diffusion coefficients in CDCl 3 (8.37±0.57×10 −10 m 2 s −1 for 9 and 7.54±0.25×10 −10 m 2 s −1 for the product).…”
Section: Resultsmentioning
confidence: 99%
“…The obvious cause is hydrogen bonding, but not necessarily as seen in the solidstate structure. A DOSY experiment showed that the molecule of 5 has a smaller hydrodynamic radius than a bona fide dimeric complex, the binuclear carbonate 34 used as internal reference. The molecular size estimated for 5 was fully consistent with a monomeric structure, suggesting an intramolecular hydrogen bond (see details in ESI).…”
Section: Methodsmentioning
confidence: 99%
“…However, in our studies of the Ni and Pd systems with the iPr PCP pincer we found that, even though the initial outcome of the reaction are the corresponding bicarbonates, 27 a and 27 b, these are labile, readily undergoing partial decarboxylation and condensation to afford the binuclear carbonates 28 a and 28 b. [96] The process is so facile that the loss of CO 2 occurs when their solutions are simply concentrated under vacuum. Full decarboxylation back to the hydroxides was observed when the carbonates were refluxed in wet THF.…”
Section: Scheme 21mentioning
confidence: 80%
“…Much of the work reported in the literature has concentrated in the reactivity of hydroxide complexes. [84,[94][95][96][97] The nucleophilic attack of the hydroxide ligand on CO 2 involves a very low energy barrier, hence it overrides the migratory insertion pathway even in coordinatively unsaturated 16-e systems, like square-planar d 8 systems. [94] This is reflected in the facile and almost instantaneous carboxylation of many types of monomeric MÀ O bonds, whereas CO 2 insertion into comparable MÀ C bonds is usually more difficult.…”
Section: Scheme 21mentioning
confidence: 99%